The Relationship between Knowledge and Attitudes of Food Handlers with the Implementation of Food Hygiene Sanitation at Restaurants in Minas District in 2022 - Haesti Sembiring; Susanti Br Perangin-Angin; Lely Mayanti Silitonga (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Food and drink are the most important necessities of life and have the potential to be contaminated with pathogenic bacteria. Factors that influence food quality are the behavior of food handlers in the application of personal hygiene and food sanitation. This study aims to determine the relationship between the knowledge and attitudes of food handlers and the application of food sanitation hygiene in restaurants in Minas District. This research is a quantitative research with cross sectional research design. The location in the research is a restaurant in Minas District. The time of this research was conducted from March to May 2022. The research population was all food handlers at restaurants in Minas District, 18 restaurants in Minas District consisting of 36 food handlers. The sampling technique is total sampling. The sample in this study were 36 people. The type of data in this study is primary data obtained by direct observation Primary data obtained from surveys to locations in restaurants in Minas District and direct interviews with respondents using questionnaires and observation sheets. Data collection was carried out by direct observation and interviews with food handlers using a questionnaire. Data analysis with chi square test. The results showed that there was a significant relationship between the knowledge of food handlers and the application of food sanitation hygiene (p-value = 0.005) and there was a significant relationship between the attitudes of food handlers and the application of food sanitation hygiene (p-value = 0.002). It is recommended that food handlers should wash their hands with soap and running water before doing work, wear masks and not chat while processing food. Keywords: Attitude, Food Handlers, Hygiene, Knowledge, Sanitation